2017
DOI: 10.1016/j.compscitech.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Highly thermally conductive flame-retardant epoxy nanocomposites with reduced ignitability and excellent electrical conductivities

Abstract: A highly efficient phenylphosphonate based flame retardant epoxy resin (FREP) was firstly prepared from phenylphosphonic dichloride (PPDCl) and allylamine (AA). Functionalized graphite nanoplatelets (fGNPs) fillers were then performed to fabricate the fGNPs/FREP nanocomposites via mixing followed by casting method. The thermally conductive coefficient (l), thermal diffusivity (a), flame retardancy, electrical conductivities and thermal stabilities of the fGNPs/FREP nanocomposites were all enhanced with the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(137 citation statements)
references
References 56 publications
1
136
0
Order By: Relevance
“…Polymer composites with GO have attracted great interest due to their unique properties, which are derived from extended interactions between the GO and the matrix and their wide potential applications such as electromagnetic wave shielding and sensors [24][25][26][27][28][29][30][31][32]. For example, Cao et al [33] found that the tensile strength and young's modulus of GO composites increased by 78 and 73%, respectively, when compared with pure polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites with GO have attracted great interest due to their unique properties, which are derived from extended interactions between the GO and the matrix and their wide potential applications such as electromagnetic wave shielding and sensors [24][25][26][27][28][29][30][31][32]. For example, Cao et al [33] found that the tensile strength and young's modulus of GO composites increased by 78 and 73%, respectively, when compared with pure polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin (EP) is a critical and low‐cost thermosetting resin with excellent mechanical, heat resistance, and solvent resistance properties, which is widely used in coatings, adhesives, electrical and electronic materials, laminates, etc . However, the flammability of EP limits its application in some areas with high safety requirements .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of nanomaterials into polymers seems to be an effective approach to improve their performances, including flame retardancy, thermal stability, and mechanical properties . Commonly, the enhancements in the physical properties are strongly dependent on the dispersion of nanomaterials .…”
Section: Introductionmentioning
confidence: 99%